THE EFFECT OF APPLYING MULTISENSORY TEACHING METHOD ON THE STUDENTS’ VOCABULARY ACHIEVEMENT IN READING - Widya Ulfa; Masitowarni Siregar; Johannes Jefria Gultom (GENRE JOURNAL : Journal of Applied Linguistics of FBS Unimed, 2015)
This study was conducted as an attempt to find out the effect of applying Multisensory Teaching Method on the students’ vocabulary achievement in reading. This research used the experimental design. The population of this research was the students of SMP Nusa Penida Medan. The Sample of this research was the 2014/2015 seventh grade students of SMP Nusa Penida Medan with the total number 60 of students as sample taken by using random sampling technique. The research was divided into two groups: experimental and control groups. The instrument used to collect the data was multiple choice tests of pre-test and post-test. To obtain the result of the reliability of the test, the Kuder Richardson formula (KR21) was used. The result of the calculation showed that the reliability of the test was high. The data were analyzed by using t-test formula. The result of the analysis showed that tvalue was higher than ttable (5, 87>2, 00) at the level of significance 0, 05 with the degree of freedom (df) 58. Therefore, null hypothesis (H0) is rejected and hypothesis alternative (Ha) is accepted. It means that there is a significant effect of using Multisensory Teaching Method on the students’ achievement in vocabulary in reading. Keyword : Multisensory Teaching Method, Vocabulary Achievement.